Multiclass Classification of Denim Fabric Defects Using Convolutional Neural Networks - Neves, Thamiris Gire Zine; Beraldo, Roberto Gutierrez; Ghedini, Cinara Guellner (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and Images, 2025)
In denim fabric manufacturing, quality assessment traditionally relies on visual inspection by weavers, as guided by ABNT NBR 13484. This manual, post-production process can delay defect detection, allowing issues to persist and recur, which disrupts the production chain. To address this, we developed a deep neural network for multiclass classification of common fabric defects, including double yarns, coarse ends, harness misdraws, slack ends, broken wefts, and soft wefts. Our model integrates convolutional layers for feature extraction and linear layers for classification. It was trained on 2,985 images captured using a low-cost camera mounted above a textile manufacturing loom in a denim manufacturing laboratory, replicating realworld inspection conditions. Our model achieved a classification accuracy of 89%, outperforming other state-of-the-art machine learning algorithms. These results demonstrate the potential for real-time defect detection during production, reducing material waste and improving overall fabric quality.